Economic Growth and Financial Development: Evidence from Panel Cointegration Tests in Emerging Countries - Gültekin, Melis; Umutlu, Mehmet (International Journal of Contemporary Economics and Administrative Sciences, 2023)
This study analyzes the long-run relationship between economic growth (EG) and financial development (FD) in 27 emerging countries over the period 1980 to 2018 by employing the Johansen-Fisher panel cointegration method. The study also performs the vector error correction model (VECM) to determine the direction of a causal relationship among the variables. Two components of the index of financial development introduced by Svirydzenka (2016), financial markets and financial institutions indices, are employed to reveal through which channels EG has a long-term association with FD. Empirical findings show a significant long-run association between EG, the overall index of FD, and its sub-indices. Furthermore, the results from panel VECMs indicate a one-way unidirectional causality between EG and the FD index, while there is a two-way causality between EG and financial markets as well as between EG and financial institutions indices in the short run. We obtain similar results with Kao and Pedroni panel cointegration tests. We also show that financial institutions and financial markets significantly affect economic growth in the long run.